Case report: A case of blood culture-negative Bartonella quintana endocarditis: blood mNGS is an efficient method for early diagnosis - Pu, Jun-fan; Zhou, Yan-ling; Deng, Min; Wu, Jing (Frontiers in Medicine, 2024)
Bartonella quintana is one of the main causes of blood culture-negative endocarditis, and routine blood culture and serological methods are difficult to achieve early diagnosis. We report a case of blood culture-negative Bartonella quintana endocarditis from southwestern Chongqing. The patient was a 67-year-old male scavenger who presented with heart failure without fever as the main clinical manifestation upon admission. He stated having had contact with stray cats in the past 2 months. The combination of clinical symptoms, echocardiography, and blood mNGS testing confirmed the infection of Bartonella quintana.